Hybrid Assembly of the Genome of the Entomopathogenic Nematode Steinernema carpocapsae Identifies the X-Chromosome. Issue 8 (1st August 2019) - Serra, Lorrayne; Macchietto, Marissa; Macias-Muñoz, Aide; McGill, Cassandra Joan; Rodriguez, Isaryhia Maya; Rodriguez, Bryan; Murad, Rabi; Mortazavi, Ali
Abstract: Entomopathogenic nematodes from the genus Steinernema are lethal insect parasites that quickly kill their insect hosts with the help of their symbiotic bacteria. Steinernema carpocapsae is one of the most studied entomopathogens due to its broad lethality to diverse insect species and its effective commercial use as a biological control agent for insect pests, as well as a genetic model for studying parasitism, pathogenesis, and symbiosis. In this study, we used long-reads from the Pacific Biosciences platform and BioNano Genomics Irys system to assemble the most complete genome of the S. carpocapsae ALL strain to date, comprising 84.5 Mb in 16 scaffolds, with an N50 of 7.36 Mb. The largest scaffold, with 20.9 Mb, was identified as chromosome X based on sex-specific genome sequencing. The high level of contiguity allowed us to characterize gene density, repeat content, and GC content. RNA-seq data from 17 developmental stages, spanning from embryo to adult, were used to predict 30, 957 gene models. Using this improved genome, we performed a macrosyntenic analysis to Caenorhabditis elegans and Pristionchus pacificus and found S. carpocapsae's chromosome X to be primarily orthologous to C. elegans ' and P. pacificus ' chromosome II and IV. We also investigated the expansion of protein families and gene expression differences between adult male and female stage nematodes. This new genome and more accurate set of annotations provide a foundation for additional comparative genomic and gene expression studies within the Steinernema clade and across the Nematoda phylum.